HYDRODYNAMIC CHARACTERISTICS OF A WAVE ENERGY CONVERTER OF DUAL VERTICAL POROUS PLATES OSCILLATING IN SURGE - Boualia, Yasmine; Chioukh, Nadji; Hamoudi, Benameur; Yuksel, Yalcin (BEGELL HOUSE INC, 2021)
To meet the basic demands of energy for future generations, oceans can deliver a substantial amount of wave energy that can be harnessed to complement other types of renewable sources. In the present study, we investigate the hydrodynamic performance of an oscillating surge wave energy converter. The system is composed of two vertical porous plates, forced to oscillate horizontally in tandem under the action of regular waves to harness wave power. The numerical results show that when the interspacing between the plates is set at odd multiples of one-quarter wavelength, the wave reflections reach their lowest values, the wave transmissions and dissipations become maximum, and the dynamic characteristics of the idealized system including plate displacements, hydrodynamic wave forces, and wave power available for extraction attain their peaks. The present idealized arrangement is found to extract optimal wave power in the shallow water region, at a primary resonant frequency that rises only when using low values of the system's damping and the plates' porosity.
Keywords: wave energy converter; vertical porous plates; oscillations; eigenfunction expansion method; power generation; coastal environment; WATER-WAVES; OBLIQUE WAVES; TRANSMISSION; REFLECTION; Mechanics